Attitudinal factors impacting local visitor perspectives on the sustainability of Borobudur Temple tourism. (13th November 2021) - Untoro, Wisnu; Sawitri, Hunik Sri Runing; ,; Sunaryo, Sinto; Aziz, Yuhanis Abdul
The development of tourism at Borobudur Temple has caused substantial environmental, economic, social, and cultural impacts. Therefore, it is crucial to establish a path toward a sustainable way to conduct tourism of this site. Previous studies have focused on local communities as a key player in the sustainable tourism development process. This study seeks to address the local visitors' perspective and assess their support for sustainable tourism development. Research data were collected from previous local visitors to Borobudur Temple. Of the 340 respondents to the online survey questionnaire, 267 met the criteria. We tested our hypothesis using PLS-SEM analysis and found that attitudes toward economic, social, and environment significantly affected support for sustainable tourism development. This study provides new insight into visitors' support of sustainable development and the factors affecting the variable.